Efisiensi Penggunaan Transportasi Publik Berbasis Rel (Literature Review) - Lestiyono, Sidik (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Rail-based public transportation is one of the primary solutions for addressing urban congestion, energy efficiency, and carbon emission reduction. This study aims to analyze the efficiency of rail transport systems through a literature review by examining previous research on operational, financial, and environmental aspects. The findings indicate that rail-based transportation has a higher efficiency level than other modes in terms of passenger capacity, speed, and environmental impact. However, major challenges include high construction and maintenance costs, integration with other transport systems, and reliance on government policies and regulations. Various innovations, such as the implementation of Internet of Things (IoT), Artificial Intelligence (AI), and Transit-Oriented Development (TOD), can enhance the efficiency of rail transport systems. This study recommends sustainable investment in infrastructure, optimization of technology-based operational systems, and policies that support public transport integration to improve efficiency and attractiveness.